Diagnostic and prognostic potential of cell-free RNAs in cerebrospinal fluid and plasma for brain tumors - Jinyong Huang; Jinxia Zhou; Jun Wang; Yonghao Yi; Lu Zhang; Shuyong Qiu; Yuanyan Tan; Qianwen Guo; Feilong Zhao; Xinying Li; Yanqin Niu; Haoyu Li; et al. (npj Precision Oncology)
Abstract Systematic assessment of the clinical applicability of cell-free RNAs (cfRNAs), which includes broader RNA categories beyond microRNAs, for patients with brain tumors remains largely unexplored due to the lack of sensitive profiling technologies. Our study endeavors to bridge this gap by utilizing an optimized cell-free transcriptome profiling technique that we have recently developed. We comprehensively profiled the cell-free transcriptome in plasma and cerebrospinal fluid (CSF) samples from a total of 85 patients with glioma, meningioma, or tumor-free central nervous system diseases. We identified 16 cfRNA signatures in CSF with robust performance in brain tumor detection (test set AUC = 0.94; validation set AUC = 1). The integration of CSF and plasma-derived cfRNAs outperformed individual analyses using either CSF or plasma candidates for the classification of glioma (test set AUC = 0.94; validation set AUC = 0.85) and meningioma (test set AUC = 0.92; validation set AUC = 0.83). Additionally, we identified 33 CSF and 3 plasma cfRNAs with prognostic significance for postoperative patient outcomes. Multivariate analysis showed that cfRNA-based risk scores (Hazard ratio=9.9) outperformed traditional risk factors in predicting recurrence-free survival. Importantly, our findings in liquid biopsies are consistent with results from primary tumor tissues. By delving into the diagnostic and prognostic implications of cfRNA signatures in CSF and plasma, our study paves the way for improved diagnostic precision and personalized therapeutic interventions for brain tumor patients.